MENYELISIK DIKSI TENTANG AKHLAK MULIA DALAM SENANDUNG DIWAN IMAM SYAFI’I TERJEMAHAN IMAM AHMAD IBNU NIZAR - Tiara Akhwatunnisa; Nani Solihati (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2022)
A writer or poet must be familiar with the term diction or word choice. Diction is an important element in literary works that the author uses to convey a message to the reader, another meaning is that the existence of diction or vocabulary selection will make it easier for the reader to accept what the author conveys. Word selection is used so as not to cause different views between the author and the reader, as well as the suitability of words in a piece of writing. The appropriate word will build an atmosphere in a literary work, besides the excessive use of vocabulary will make it difficult for the reader to interpret the message of the author. The term use of diction is not very well known by the general public. For this reason, with this research, it is hoped that it will be able to introduce and enrich vocabulary through diction to the general public. In most of the verses asy-Syafi'i contain life instructions, noble behavior for a Muslim, wisdom, various favors, and the nature of zuhud in the world. The purpose of this writing is to find out and describe the use and type of diction in the verses of Diwan Imam Syafi'i, with a qualitative descriptive method using stylistic studies. The results of this study show that translators use words that are synonymous with the original verse to simplify the meaning of each translation.